Uso de carvão de ossos bovinos na remoção de contaminantes orgânicos de concentrados de eletrodiálise e sua contribuição ao reuso de água na indústria de petróleo - Patricia da Luz Mesquita (2016)
In a scenario of hydric scarcity, water reuse is essential to minimize make-up; however, bincreased salinity comes along with recycling the streams. Crystallization has been evaluated to remove dissolved ions; nevertheless, contaminants affect its efficiency. In this context, the removal of residual organics from the saline concentrate fromelectrodialysis applied for water reuse in a Brazilian petroleum refinery was investigated. Aiming at establishing a sustainable virtuous circle, bone char, a waste from food industry, 12.0 32.0 mesh (0.5 to 1.4mm) particle size, mesoporous structure, was used as adsorbent and was able to remove, partially, refractory organics in the effluent, a complex mixture of long chain hydrocarbons (C10-C50), aromatic compounds,carboxylic acids, amines and amides . Equilibrium adsorption time of 4 hours was determined from batch experiments (through 72 hours, at 25.0±0.1°C, pH=7.6±0.5 and 200±1 rpm, solid/liquid ratio of 10g.kg-1) in a shaker and a removal of 45% for dissolved chemical oxygen demand (COD) was observed in these operational conditions. Pseudosecondorder model for kinetics (R2=0.9993; k2=0.0184mg-1.min-1; qe=3.21mg.g-1) best described the system and Freundlich isotherm model best fitted to experimental data, suggesting physisorption in multiple heterogeneous layers. The adsorbent thermal andchemical regeneration was possible and the best methodologies, among the investigated, were 300ºC, 60 minutes in a furnace and 0.15mol.L-1 NaOH solution, for 30 minutes, with, respectively, 66% and 94%, of recovery of percentual COD removal capacity, compared to new bone char, after the first cycle of regeneration. For the processdynamics, maximum adsorption capacity of refractory organics in fixed-bed column of bone char increased with increasing bed depth, decreasing flow rate and reduction of the initial concentration, reaching 22,92mg.g-1 for the deepest bed tested (12,9cm). However, breakthrough curves profile indicated that the C-EDR effluent contains organic compounds which can be adsorbed by the bone char, but others that can not. Scaling up was possible for the C/Co ratios of 0.55, 0.60 and 0.65, providing a service time at about 16 days for the first case (45% removal efficiency) for typical real conditions column dimensions and effluent flow rates used in the refinery.